An Analysis of Gender Equality of Chinese Culture in Mulan Film (2020) - Sirikit A. Usman; Meis Sintia Umar; Mifta Sulistia Tamola; Ridho Ishak (NOTION: Journal of Linguistics, Literature, and Culture, 2021)
Mulan film (2020) raises gender issues and is still related to the laws of norms and traditions. Mulan has a strong and patriarchal nature while Chinese cultural traditions are not unilateral with Mulan figures. The study aims to promote justice for women with regard to Chinese culture and traditions, as well as whether it has the opportunity to promote equal treatment without discrimination. Gender equality is commonplace to raise and talk about. Each gender is formed in a complex culture of each gender either in their respective positions or positions. Gender equality is linked to feminist, masculine and also includes sexism. Women and men can change roles like women can be wise leaders and men can do the skills that women have such as cooking. This study uses qualitative descriptive methods to analyze the social circumstances associated with the scene. Researchers use the technique of observing the film, interpreting each situation in the film, then collecting data, seeking information on gender equality or activities through observation and sensing that are still related to gender equality in culture, After that give a view on the object to be observed. Thus the research of Mulan film (2020) is intended to find a new mindset or an idea and a new understanding. This method uses observation and sensing and then provides a new interpretation.